EVALUASI PENGGUNAAN OBAT ANTIPLATELET TERHADAP KEJADIAN PERDARAHAN SALURAN CERNA BESERTA FAKTOR RISIKONYA PADA PASIEN STROKE - Martha Evy Susanti, Rizaldy Pinzon, Sugiyanto (NEURONA, 2014)
INTRODUCTION ANTIPLATELET THERAPY IS WIDELY USED IN PATIENTS WITH ISCHEMIC STROKE THE USE OF ANTIPLATELET IS RECOMMENDED TO REDUCE THE INCIDENCE OF RECURRENT STROKE AND OTHER CARDIOVASCULAR EVENTS ONE SIDE EFFECT OF ANTIPLATELETS IS GASTROINTESTINAL BLEEDING THAT CAN INCREASE MORTALITY